How important is healthiness, carbon footprint and meat content when purchasing a ready meal? Evidence from a non-hypothetical discrete choice experiment. (1st February 2021) - Macdiarmid, Jennie I.; Cerroni, Simone; Kalentakis, Dimitrios; Reynolds, Christian
Abstract: Recent high-level reports state the population should decrease meat consumption to reduce greenhouse gas (GHG) emissions, as well as improve public health. This calls for new strategies to change dietary habits, especially as many consumers are reluctant to eat less meat. This study tests the effect of labelling a meat-based ready meal with different levels of carbon footprint and healthiness on consumers' willingness to pay (WTP) for these attributes. Participants took part in two sequential non-hypothetical discrete choice experiments (DCE). In the first experiment, they completed a DCE where the ready meals (i.e. beef lasagne) were labelled using a dual traffic light labelling system; one labelled for carbon footprint and one for healthiness. In the second experiment, participants repeated the DCE after they were told the carbon footprint and healthiness varied because of the meat and saturated fat content, respectively. The study found that participants were willing to pay a premium for the healthier lasagne and this did not change when they were given the information about saturated fat content. Participants were also willing to pay a premium for lasagne with a lower carbon footprint, but this decreased when they knew these meals contained less meat. Information about the meat content had the unintended consequence of discouraging people to buy lasagne with a low carbon footprint. The study provides an important insight for policy and industry into the effect of labelling information on consumers' purchasing decisions at a time when people are being encouraged to eat less meat. Highlights: Consumers will pay a higher premium for healthier and lower carbon footprint meals. There is no clear preference for carbon footprint or healthiness in choosing a meal. Knowledge of the meat content reduces WTP for a meal with a lower carbon footprint. Reducing the saturated fat content of a meal is more acceptable than reducing meat. Expected tastiness influences the WTP for meals when the meat content is disclosed.